2010
DOI: 10.1111/j.1475-2743.2010.00291.x
|View full text |Cite
|
Sign up to set email alerts
|

The Irish Agricultural Catchments Programme: catchment selection using spatial multi‐criteria decision analysis

Abstract: The Nitrates Directive is a European Union legislative framework for managing agricultural nutrient transfers from land to water and, in the Republic of Ireland, is the main Programme of Measures for agriculture in the Water Framework Directive regulations. As part of the requirement for evaluating the Nitrates Directive National Action Programme and an associated derogation for intensive grassland farming, Ireland is monitoring environmental and economic effectiveness at the catchment scale. The selection of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 25 publications
0
36
0
1
Order By: Relevance
“…Catchments generally ranged from 4 km 2 to 12 km 2 and the criteria used for selection included maximisation of agricultural intensity (based on percentage arable or forage area and livestock grazing intensity), minimisation of non-agricultural land uses (residential housing density) and the selection of a range of high N or P transport risky landscapes. The MCDA process is described in detail by Fealy et al, (2010).…”
Section: Methodsmentioning
confidence: 99%
“…Catchments generally ranged from 4 km 2 to 12 km 2 and the criteria used for selection included maximisation of agricultural intensity (based on percentage arable or forage area and livestock grazing intensity), minimisation of non-agricultural land uses (residential housing density) and the selection of a range of high N or P transport risky landscapes. The MCDA process is described in detail by Fealy et al, (2010).…”
Section: Methodsmentioning
confidence: 99%
“…The program is designed to assess the effectiveness of measures well before improvements are expected to translate into improved water quality in the f inal aquatic receptors, which in some cases may take up to twenty years (Schulte et al 2010b). In the first stage, four catchments (two arable and two grassland catchments) from 1500 possible candidates were selected to be included in the study using spatial multi-criteria decision analysis (Fealy et al 2010). Combined, the four catchments represent the range of intensive grassland and arable agriculture interests in Ireland across a soil and physiographic gradient that defines the potential risk of P and/or N transfers (Fealy et al 2010).…”
Section: Catchment-scale Researchmentioning
confidence: 99%
“…Research is starting to emerge in this area, for example, recent research by Jordan et al, (2011;2012) in a study of 4 intensively instrumented Irish agricultural catchments (2 grassland and 2 arable -Fealy et al, 2010;Wall et al, 2011) found that in the context of slurry spreading the closed periods represent approximately 25% of annual rainfall. However, the nutrient losses observed during the closed period in this dataset were all greater than 25% and up to 48% of the annual export of total P and 50% of nitrate.…”
Section: Discussionmentioning
confidence: 99%
“…The ND is a precursor of the Water Framework Directive (OJEC, 2000) and aims to minimise surplus P and N losses from agriculture to the aquatic environment. Nutrients in fertilisers promote plant growth but application in excess of plant requirement can cause negative environmental externalities such as eutrophication (EPA, 2008) As outlined by Fealy et al (2010) the GAP regulations address the need for managing both potential point and diffuse sources of nutrient transfers from agricultural land.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation